Environmental regulations as industrial policy: Vehicle emission standards and automotive industry performance. Issue 131 (May 2022) - Li, Xin; Nam, Kyung-Min
Abstract: In this paper, we examine a potential causal link between vehicle emission standards and local automotive industry performance, using a 42-country panel data set covering a 19-year period between 2000 and 2018. Our panel logit analysis shows that having a sizeable local automotive industry decreases the chance of adopting stringent vehicle emission standards, while the stock of automotive FDI increases the chance. This finding suggests that the primary motivations for vehicle emission standards may not be purely environmental. Our follow-up Granger causality test demonstrates that such non-environmental motivations have in fact translated into an actual industry-promotion outcome. Stricter emission standards in OECD member countries tend to promote local automotive output and international vehicle export with a 3-year time lag, while this causal link is limited to up-market exports for non-OECD panels. Automotive FDI hosts with large domestic markets and/or local-brand automakers also present a similar causal link, but in this case significant long-term industry-promotion effects appear only after a short-term negative shock. These results suggest that a regulation-induced short-term efficiency loss may be partly offset by a long-term productivity gain through advance/timely local adoption of cleaner technologies. Highlights: Vehicle emission standards involve non-environmental motivations, as well. Local production volume and FDI stock affect the stringency of the standards. Regulation-induced efficiency loss can be partly offset by long-term productivity gain. Stricter standards tend to have pro-export effects with a 3-year lag. The causal link depends on domestic market size and local-brand automakers.